O gesto do arranjador na música popular - Rafael Andrade Martini (2017)
This work presents an analysis of the activity of the arrangers in the field of popular music, in order to verify the role of the arrangements as an important vector of language development within this universe. Based on concepts drawn from the theory of Dialogism, from linguist Mikhail Bakhtin, the Hybridization theory, from anthropologist Néstor Garcia Canclini, academic research on arrangement, as well as the speeches of some non-academic musicians, the dissertation offers an observation about the causes and consequences of the work of some arrangers who have made transformational fusions in the field of popular Brazilian music, especially those who have taken Afro-Brazilian music and culture as the raw material or basis on these fusions. With a more particular focus on the arrangements of Letieres Leite, written for his Orkestra Rumpilezz, the work still brings two of these arrangements analyzed in light of the concepts related here.